Association Between 25-hydroxyvitamin D Levels and Testosterone in Healthy, Non-Obese, Young Adult, Filipino Men - Buenaluz-Sedurante, Myrna; Bruno, Racquel; Dagang, Daryl Jade; Co, Mark Isaiah; Tee, Michael (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Objective. This study seeks to determine the association between vitamin D and testosterone in healthy, adult Filipino males. Methodology. This cross-sectional study included 110 healthy, non-obese, male volunteers aged 21–40. History and physical exam were taken, and blood was drawn for vitamin D, total testosterone (TT), sex hormone binding globulin (SHBG), albumin, insulin, fasting plasma glucose, and total cholesterol. Free testosterone (FT) was calculated. Vitamin D data were classified by status and TT, FT, and SHBG levels were compared using the Kruskal–Wallis’s test. The associations of vitamin D levels with TT, FT, and SHBG were explored using multiple regression analysis. Results. Vitamin D levels were sufficient in 3 (2.7%), insufficient in 17 (15.45%), and deficient in 90 (81.8%) of the sample. There were no significant differences in the mean TT (p=0.7981), FT (p=0.8768), nor SHBG (p=0.1838) across vitamin D status. Vitamin D was not associated with TT nor FT before or after adjustment for age and age plus body mass index (BMI). Vitamin D was associated with SHBG before and after the aforementioned adjustments, but this became insignificant on sensitivity analysis. Conclusion. There is no association between vitamin D and TT, FT nor SHBG in our cohort with deficient Vit D levels.